Parenting stress, perceived social support and children behavioural concern of parent with different development children in Malaysia. - Lee, Ik Hui; Teh, Wan Xin; Wong, Jean Ann (2019)
The aim of this study is to compare whether a child’s physical characteristics, parents’ perceived social support and child’s behavioural concern predicts on parenting stress. The child’s physical characteristic includes children with disabilities without physical characteristics, children with typical development and children with disabilities with physical characteristics. Total sample sizes of 150 participants were recruited, in which all are female participants with children of either three different physical characteristics. The age range for their children was between 4–16 years old in lieu of the requirement for Strengths and Difficulties Questionnaire (SDQ). This study was a quantitative study using survey questionnaire in research method and conducted using cross-sectional design. The questionnaire consists of four sections which are demographic information, Parental Stress Scale, Multidimensional Perceived Social Support Scale and Strengths and Difficulties questionnaire. Results indicated that perceived social support and child’s behavioural concern strongly predicts the parenting stress, whereas for child’s physical characteristics, parents of children with disabilities without physical characteristics and parents of children with typical development was not a good predictor on parenting stress. This study brings theoretical contributions as it fills in the research gap on comparison of parents of children with different learning needs on their parenting stress level, perceived social support and child’s behavioural concern. This research had studied on whether child’s physical characteristics, parents’ perceived social support and child’s behavioural concern predicts on parenting stress.